2006
DOI: 10.1152/jn.00578.2005
|View full text |Cite
|
Sign up to set email alerts
|

Shift of Intracellular Chloride Concentration in Ganglion and Amacrine Cells of Developing Mouse Retina

Abstract: GABA and glycine provide excitatory action during early development: they depolarize neurons and increase intracellular calcium concentration. As neurons mature, GABA and glycine become inhibitory. This switch from excitation to inhibition is thought to result from a shift of intracellular chloride concentration ([Cl-]i) from high to low, but in retina, measurements of [Cl-]i or chloride equilibrium potential (ECl) during development have not been made. Using the developing mouse retina, we systematically meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 66 publications
8
86
1
Order By: Relevance
“…1C and Fig. S1A), in agreement with previously reported data (22). This early depolarizing action of GABA is not prevented by addition of the alternate energy substrate pyruvate (Table S1), in contrast to recent observations in both neocortex (11) and hippocampus (26).…”
Section: Gaba Switch Occurs Normally In Nicotinic Acetylcholine Recepsupporting
confidence: 93%
See 2 more Smart Citations
“…1C and Fig. S1A), in agreement with previously reported data (22). This early depolarizing action of GABA is not prevented by addition of the alternate energy substrate pyruvate (Table S1), in contrast to recent observations in both neocortex (11) and hippocampus (26).…”
Section: Gaba Switch Occurs Normally In Nicotinic Acetylcholine Recepsupporting
confidence: 93%
“…Calcium imaging has been established as a preferred method forassaying depolarizing effects because imaging allows us to monitor depolarization in many neurons simultaneously without perturbing [Cl − ] i . Several previous studies in RGCs have confirmed this approach by demonstrating that an increase in intracellular calcium concentration in response to activation of GABA A receptors corresponds to an E GABA that is depolarized compared with the resting membrane potential as determined by perforated patch recordings (15,22,23).Retinal neurons loaded with Oregon Green BAPTA-1 (OGB-1) acetoxymethyl ester (AM) displayed an increase in intracellular calcium concentration ([Ca 2+ ] i ) in response to short applications of depolarizing, high K + -containing solution ( Fig. 1 A and B).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…KCC2 labeling was present in the OPL and INL, but failed to colocalize with SV2 in photoreceptor terminals; instead, the labeling was present in the post-synaptic sites of photoreceptor terminals and the INL. The absence of KCC2 in the photoreceptor terminals is similar to previous results in rat and primate retinas (Vu et al, 2000;Vardi et al, 2000), but not ferret retinas in which KCC2 is detected in photoreceptors (Zhang et al, 2006a(Zhang et al, , 2006b). …”
Section: Nkcc1 In Photoreceptor Terminals In Adult Mouse Retinassupporting
confidence: 90%
“…These results suggest that accumulating intracellular Cl − might have occurred when photoreceptor synapses were formed. However, we do not know whether KCC2 is transiently expressed in photoreceptors during development, as suggested in ferret retinas (Zhang et al, 2006a(Zhang et al, , 2006b). …”
Section: The Expression Of Nkcc1 In the Distal Retinal Synaptic Develmentioning
confidence: 88%